EVALUATION OF ANTIMICROBIAL ACTIVITY OF PITHECELLOBIUM DULCE POD PULP EXTRACT - PRADEEPA, S.; SUBRAMANIAN, S.; KAVIYARASAN, V. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
ABSTRACT Objective: Diseases due to pathogenic bacteria and fungi represent a critical problem to human health and they are the major cause of morbidity and mortality worldwide. Plants based antimicrobials are effective in the treatment of infectious diseases while simultaneously mitigating many of the side effects that are often associated with synthetic antimicrobials. In the series of medicinal plants, one such medicinal plant which has been widely used in traditional medicine but lacks scientific scrutiny is Pithecellobium dulce. The present study was aimed to investigate the antimicrobial properties of P.dulce pod pulp extract against common pathogenic gram positive, gram negative bacteria and fungi. Methods: Ethanolic extract was used for the study. Phytochemical screening, total phenolic and flavonoid content were determined. The antibacterial and antifungal activity of ethanolic extract of pod pulp was tested against clinically important Gram positive, Gram negative bacteria and pathogenic fungal strains. The inhibitory effect was assessed by well diffusion method. The Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and Minimum Fungicidal Concentration (MFC) were also determined by serial dilution method. Results: Â Phytochemical analysis of the pulp extract revealed the presence of alkaloids, flavonoids, glycosides, saponins, phytosterols, and triterpenoids. The pulp extract was found to contain significant amounts of total phenols and flavonoids. The pulp extract showed significant zone of inhibition in a dose dependent manner. The MIC and MBC values of the pulp extract against both Gram positive and Gram negative bacterial strains varies from 1mg to 5mg and the results are comparable with chloramphenicol. The MIC and MFC values of pod pulp extract against fungal strains varies from 1 mg to 7 mg and the results are comparable with Amphotericin B. Conclusion: It can be concluded that the pulp extract possesses potent bactericidal and fungicidal activity which in turn may be due to the presence of biologically active ingredients with antimicrobial activity in the pod pulp. Keywords: Pithecellobium dulce; Antibacterial; Antifungal; Minimum Inhibitory concentration